Újrajátszani, ami nem történt meg: A performatív múltfikciók nemzetközi és magyar példái - Fazakas, Gergely Tamás (Studia Litteraria, 2024)
This paper examines acts and artefacts that can be interpreted as performative statements. I focus on international and Hungarian, artistic and partly amateur re-enactments, as well as on fiction and works of history writing that can be considered pseudo-historical, counterfactual or, in Sylvia Sasse and Inke Arns’s term, “as-if ”-reenactments in their entirety or to some extent. These performative accounts of the past, both in the artistic and in non-artistic fields, have not been systematically investigated in reenactment studies.